Men's role within the women's movement to achieve gender equality in Indonesia: Threat or opportunity? - Rihi, Ryan Richard; Poerwandari, Elizabeth Kristi (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
The women's movement, both globally and locally in Indonesia, has organically been trying to eliminate gender inequality caused by patriarchy for a long time. Even though they benefit from patriarchal culture in many ways, men also experience losses and, as a result, are interested in getting involved in the gender equality movement, which women mostly initiate. However, men are in a dilemma position in this women's movement: as a threat and an opportunity. Therefore, this article is qualitative research that explores the potential and risks of men's involvement in the women's movement through a literature review. All the collected articles were then read, and their important findings were formulated in the results and classified thematically. The results show that historically, men have been and continue to be involved in the gender equality movement. However, several pros and cons arise. Therefore, this article also ultimately argues that even though it is significant for men to be involved in the women's movement to end all forms of oppression, domination, and violence, the involvement of men is conditional, which pays attention to the safety of women and is not intended to take over the political position of the leader of the gender equality movement from women.